A Simple Assay to Assess Salmonella enterica Persistence in Lettuce Leaves After Low Inoculation Dose - Oblessuc, Paula Rodrigues; Melotto, Maeli (Frontiers in Microbiology, 2020)
Salmonella enterica is an enterobacterium associated with numerous foodborne illnesses worldwide. Leafy greens have been a common vehicle for disease outbreaks caused by S. enterica. This human pathogen can be introduced into crop fields and potentially contaminate fresh produce. Several studies have shown that S. enterica can survive for long periods in the plant tissues. Often, S. enterica population does not reach high titers in leaves; however, it is still relevant for food safety due to the low infective dose of the pathogen. Thus, laboratory procedures to study the survival of S. enterica in fresh vegetables should be adjusted accordingly. Here, we describe a protocol to assess the population dynamics of S. enterica serovar Typhimurium 14028s in the leaf apoplast of three cultivars of lettuce (Lactuca sativa L.). By comparing a range of inoculum concentrations, we showed that vacuum-infiltration of a bacterium inoculum level in the range of 3.4 Log CFU.mL-1 (with a recover of approximately 170 cells per gram of fresh leaves 2 hours post inoculation) allows for a robust assessment of bacterial persistence in three lettuce genotypes using serial dilution plating and qPCR methods. We anticipate that this method can be applied to other leaf-human pathogen combinations in an attempt to standardize the procedure for future efforts to screen for plant genetic variability, which is useful for breeding programs.